2016
DOI: 10.1021/acs.langmuir.6b03249
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Ethylene-Bridged Polymethylsiloxane Aerogels and Xerogels with Improved Bending Flexibility

Abstract: Transparent, monolithic aerogels with nanosized colloidal skeletons have been obtained from a single precursor of 1,2-bis(methyldiethoxysilyl)ethane (BMDEE) by adopting a liquid surfactant and a two-step process involving strong-acid, followed by strong-base, sol-gel reactions. This precursor BMDEE forms the ethylene-bridged polymethylsiloxane (EBPMS, O(CH)Si-CHCH-Si(CH)O) network, in which each silicon has one methyl, two bridging oxygens, and one bridging ethylene, exhibiting an analogous structure to that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
47
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 35 publications
6
47
0
2
Order By: Relevance
“…[32,33] However,t he limited bending flexibility and functionality of the aerogels are yet to be satisfactory. Moreover,t he poor processability of traditional aerogels significantly restricts their practical applications.T herefore, apreparation of multifunctional aerogels combined with high mechanical properties including processability still remains ag reat challenge.In our previous papers,i thas been reported that controlled hydrolysis and condensation of trifunctional organoalkoxysilanes and organo-bridged alkoxysilanes can afford transparent nanoporous polyorganosilsesquioxane [34][35][36] and organo-bridged polysiloxane [37,38] aerogels with good compressibility,e lasticity,a nd thermal insulation properties. Moreover,a no rganic-inorganic double-cross-linking approach has been found to prepare transparent polyvinylpolymethylsiloxane (PVPMS), polyallypolymethylsiloxane (PAPMS), polyvinylpolysilsesquioxane (PVPSQ), and polyallypolysilsesquioxane (PAPSQ) aerogels with high flexibility, processability,a nd excellent thermal insulation properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[32,33] However,t he limited bending flexibility and functionality of the aerogels are yet to be satisfactory. Moreover,t he poor processability of traditional aerogels significantly restricts their practical applications.T herefore, apreparation of multifunctional aerogels combined with high mechanical properties including processability still remains ag reat challenge.In our previous papers,i thas been reported that controlled hydrolysis and condensation of trifunctional organoalkoxysilanes and organo-bridged alkoxysilanes can afford transparent nanoporous polyorganosilsesquioxane [34][35][36] and organo-bridged polysiloxane [37,38] aerogels with good compressibility,e lasticity,a nd thermal insulation properties. Moreover,a no rganic-inorganic double-cross-linking approach has been found to prepare transparent polyvinylpolymethylsiloxane (PVPMS), polyallypolymethylsiloxane (PAPMS), polyvinylpolysilsesquioxane (PVPSQ), and polyallypolysilsesquioxane (PAPSQ) aerogels with high flexibility, processability,a nd excellent thermal insulation properties.…”
mentioning
confidence: 99%
“…Thedoubly cross-linked structure of the resulting aerogels is evidenced by the NMR and FTIR spectra (Figure 2a and Figure S1). As shown in the NMR spectra, the peaks located at around 7.6 and 12.6 ppm correspond to M 1 (CH 2 CH(Si-(CH 3 ) 2 O 1/2 )) n and M 0 species, [41] respectively,i ndicating the presence of polydimethylsiloxanes and aliphatic hydrocarbon chains in the PVPDMS-based aerogels.T he broad peak located at around À21 ppm corresponds to D 2 (CH 2 CH(Si-(CH 3 )O 2/2 )) n and D 1 species, [37] indicating the presence of polymethylsiloxanes and aliphatic hydrocarbon chains in PVPDMS/PVPMS composite aerogels PA 2, PA 3, and PA 4. In addition, the peak corresponding to M 1 becomes smaller while that corresponding to D 2 becomes more intense with the decrease of the molar ratio of VDMMS to VMDMS in the precursors.T his indicates that the doubly cross-linked structure contains less polydimethylsiloxanes and more polymethylsiloxanes with the increase of the amount of VMDMS in the precursors.A sp resented in the FTIR spectra, the absorption bands corresponding to CÀH, SiÀC, and Si-O-Si bonds indicate the presence of the aliphatic hydrocarbon chains and/or methyl groups and polysiloxanes of the PVPDMS-based aerogels.…”
mentioning
confidence: 99%
“…As shown in Figure 2a,b and the multiple peak fitting of the NMR spectra ( Figure S1), the intense peaks located at around -64, -66, -19, and -22 ppm correspond to T 3 (CH2CH(SiO3/2))n and T 2 species 16 in the PVPSQ aerogels, T 3 (CH2CH(CH2SiO3/2))n and T 2 species 34 in the PAPSQ aerogels, D 2 (CH2CH(Si(CH3)O2/2))n and D 1 species in the PVPMS aerogels, and D 2 (CH2CH(CH2Si(CH3)O2/2))n and D 1 species in the PAPMS aerogels, respectively. 19 For PAPMS aerogels, the small peak at around -36 ppm is attributed to a small amount of silicon with unpolymerized allyl groups in CH2=CHCH2Si(CH3)O2/2. For PVPMS and PAPMS aerogels, the small peak recognized at around -68 ppm can be attributed to T 3 (RSiO3/2, R may be methyl) species that are probably derived from the reaction between allylsilane or vinylsilane and silanol to form a siloxane bond and T silicon.…”
Section: Resultsmentioning
confidence: 99%
“…17,18 Benefiting from the organic bridge and its homogenous distribution in the network, some of them show bendability. [19][20][21] Nonetheless, their limited bendability still could not meet the need of practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Aerogels composed of this class of promising organo‐bridged polymethylsiloxane network have been recently reported by the authors’ group . Starting from 1,2‐bis(methyldiethoxysilyl)ethane (BMDEE) as the single precursor, transparent aerogels with an ethylene‐bridged polymethylsiloxane (EBPMS) network have been successfully prepared by a two‐step acid–base sol–gel process in EH‐208 (Figure a), a synthetic approach similar to the PESQ and PVSQ systems.…”
Section: Aerogels From Organobridged Alkoxysilanesmentioning
confidence: 99%